Synergic combination of the sol–gel method with dip coating for plasmonic devices - Cristiana Figus; Maddalena Patrini; Francesco Floris; Lucia Fornasari; Paola Pellacani; Gerardo Marchesini; Andrea Valsesia; Flavia Artizzu; Daniela Marongiu; Michele Saba; Franco Marabelli; Andrea Mura; et al. (Beilstein Journal of Nanotechnology, 2015)
Biosensing technologies based on plasmonic nanostructures have recently attracted significant attention due to their small dimensions, low-cost and high sensitivity but are often limited in terms of affinity, selectivity and stability. Consequently, several methods have been employed to functionalize plasmonic surfaces used for detection in order to increase their stability. Herein, a plasmonic surface was modified through a controlled, silica platform, which enables the improvement of the plasmonic-based sensor functionality. The key processing parameters that allow for the fine-tuning of the silica layer thickness on the plasmonic structure were studied. Control of the silica coating thickness was achieved through a combined approach involving sol–gel and dip-coating techniques. The silica films were characterized using spectroscopic ellipsometry, contact angle measurements, atomic force microscopy and dispersive spectroscopy. The effect of the use of silica layers on the optical properties of the plasmonic structures was evaluated. The obtained results show that the silica coating enables surface protection of the plasmonic structures, preserving their stability for an extended time and inducing a suitable reduction of the regeneration time of the chip.